Sublime Communication Technologies - Giblett, Rod. author. aut Link
XIV, 218 p.
Keywords: This lively new study is a critical cultural history of communication technologies, from railways and telegraphy to computers and the Internet, in which Rod Giblett argues that these technologies play a pivotal role in the cultural history of modernity and its project of the sublime.